#MeToo as a Connective Movement: Examining the Frames Adopted in the Anti-Sexual Harassment Movement in China. (October 2021) - Li, Pengxiang; Cho, Hichang; Qin, Yuren; Chen, Anfan
This study was aimed to contribute to understanding how networked yet fragmented online actors create meaning in digital media–enabled movements like #MeToo. By drawing upon a multidimensional framing analysis, this study investigated how personal action frames, collective action frames, and issue-specific frames were adopted in #MeToo movement in China, and it also shed light on how different groups of social actors respond to sexual harassment issues on Sina Weibo, a Chinese social media platform. This study employed computational content analysis to extract frames from a huge amount of traceable data (i.e., 16, 187 Weibo posts) and uncovered seven specific types of frames categorized as personal experiences and emotional commentary (as personal action frames), injustice and opposition (as collective action frames), and problem definition, treatment recommendation, and related news (as issue-specific frames). The results revealed that personal action frames and collective action frames were widely adopted by females and ordinary users, whereas issue-specific frames were more commonly applied by males and organizational users. These empirical findings enhance our understanding of meaning construction with regard to digital media–enabled movements.